2010
DOI: 10.1007/s00040-010-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment-dance signals draw larger audiences when honey bee colonies have multiple patrilines

Abstract: Honey bee queens (Apis mellifera) who mate with multiple males produce colonies that are filled with numerous genetically distinct patrilines of workers. A genetically diverse colony benefits from an enhanced foraging effort, fuelled in part by an increase in the number of recruitment signals that are produced by foragers. However, the influence of patriline diversity on the attention paid to these signals by audiences of potentially receptive workers remains unexplored. To determine whether recruitment dances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Tracking an entire colony over a long time would allow one to investigate the stability of task allocation. Prior research has shown that during each life stage, an individual spends most of its time in a specific nest region 31 , 54 , interacting with nestmates, but with whom they interact may depend on more than location alone (e.g., previous interactions, or the genetic diversity within the colony 55 , 56 ). Social interactions permit an exchange of information and can have long-term effects on an individual’s behavior 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Tracking an entire colony over a long time would allow one to investigate the stability of task allocation. Prior research has shown that during each life stage, an individual spends most of its time in a specific nest region 31 , 54 , interacting with nestmates, but with whom they interact may depend on more than location alone (e.g., previous interactions, or the genetic diversity within the colony 55 , 56 ). Social interactions permit an exchange of information and can have long-term effects on an individual’s behavior 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Tracking an entire colony over a long time would allow one to investigate the stability of task allocation. Prior research has shown that during each life stage, an individual spends most of its time in a specific nest region (Johnson 2010; Seeley 1982), interacting with nestmates, but with whom they interact may depend on more than location alone (Farina 2000; Girard et al 2011). Social interactions permit an exchange of information and can have long-term effects on an individual’s behavior (Cholé et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, if a colony is genotypically diverse, then foragers of all stripes (including those who rely on waggle dances to learn about the profitability of a food source) tend to visit a food source in greater numbers and often at faster rates (this study; Mattila and Seeley 2010), producing upon return to their colonies more chemical signals that spur forager reactivation (Gilley et al 2012;Carr-Markell et al 2013) and more waggle dances (this study; Mattila et al 2008;Seeley 2010, 2011). Moreover, the dances produced in genotypically diverse colonies are better attended by dance followers (Girard et al 2011) and result in a greater number of recruits arriving at the food source (this study). These interactions, which are powered by the interplay between the responsiveness of genetic specialists to foraging-related stimuli (Table I) and the allocation of foragers to high-quality food sources through intensified use of recruitment signals (Seeley and Visscher 1988), fuel a honey bee colony's competitive ability to discover, exploit, and mass recruit to patchy and ephemeral food sources.…”
Section: Discussionmentioning
confidence: 69%